Latest Insights on the Etiology and Management of Primary Adrenal Insufficiency in Children - (:unkn) unknown (GALENOS YAYINCILIK, 2018)
Primary adrenal insufficiency (PAI) is a heterogeneous group of disorders characterized by an impaired production of cortisol and other steroid hormones by the adrenal cortex. Most of the causes of PAI in childhood are inherited and monogenic in origin and are associated with significant morbidity and mortality whenever the diagnosis and treatment is delayed. Therefore, early and accurate diagnosis would allow appropriate management for the patients and genetic counselling for the family. Congenital adrenal hyperplasia accounts for most cases of PAI in childhood, followed by abnormalities in the development of the adrenal gland, resistance to adrenocorticotropin hormone action and adrenal destruction. In recent years, the use of genome-wide, next-generation sequencing approaches opened new avenues for identifying novel genetic causes in the PAI spectrum. Understanding the genetic basis of adrenal disorders is key to develop innovative therapies for patients with PAI. The promising progress made in congenital adrenal hyperplasia treatment brings new perspectives for personalized treatment in children with PAI. The aim of this review is to characterize recent advances in the genetics and management of PAI in children.
Keywords: Primary adrenal insufficiency; children; etiology; treatment; STEROIDOGENIC FACTOR-I; SUBCUTANEOUS HYDROCORTISONE INFUSION; FAMILIAL GLUCOCORTICOID DEFICIENCY; CLASSIC 21-HYDROXYLASE DEFICIENCY; DUAL-RELEASE HYDROCORTISONE; HYPOGONADOTROPIC HYPOGONADISM; NEPHROTIC SYNDROME; ADDISONS-DISEASE; MUTATIONS CAUSE; HYPERPLASIA